Approaching Emily Dickinson : critical currents and crosscurrents since 1960 - White, Fred D., 1943- (Studies in American literature and culture. Literary criticism in perspective., 2008)
When Klaus Lubbers's Emily Dickinson: The Critical Revolution appeared in 1968, examining Dickinson criticism from 1886 to 1962, a second revolution in Dickinson criticism was already gathering force. In the years since Lubbers's survey, approximately one hundred books - monographs, bibliographies, biographies, essay collections - about Dickinson and her oeuvre have appeared, making her one of the most extensively studied poets in American history. This book provides an examination of that vast body of scholarship The book gives attention to the principal trends in Dickinson scholarship during the past half-century: rhetorical and stylistic analysis of the poems and letters; biographical studies informed by theories of gender, sexuality, and by medical history; feminist studies of the poet's life and work; textual studies of the bound and unbound fascicles and the so-called worksheet drafts (or "scraps"); new assessments of the poet's social and cultural milieu, including influences on her spiritual sensibility; and of her theories of poetry, including lyricism.--description adapted from jacket